1997
DOI: 10.1002/(sici)1097-0215(19971210)73:6<891::aid-ijc22>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activity of CPT-11 in experimental human ovarian cancer and human soft-tissue sarcoma

Abstract: CPT‐11, a semi‐synthetic derivative of camptothecin, was investigated for its activity in panels of 15 human ovarian‐cancer lines and 10 human soft‐tissue sarcoma lines grown s.c. in nude mice. Various factors were analyzed that may be of influence on the extent of tumor‐growth inhibition induced by CPT‐11. At equitoxic doses, CPT‐11 was more effective in the daily ×5 schedule than the weekly ×2 schedule, although a 2‐fold higher dose was administered in the weekly ×2 schedule. Since i.p. and i.v. injections w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…This schedule was chosen because multiple investigators have demonstrated the superior preclinical efficacy of irinotecan when given in smaller divided doses compared with large single infusions (9,(35)(36)(37)(38). In addition, this schedule was used in the xenograft studies of this drug combination (21,24) and has been shown to be feasible, safe, and active in the Phase I (10) and II (13) settings.…”
Section: Discussionmentioning
confidence: 99%
“…This schedule was chosen because multiple investigators have demonstrated the superior preclinical efficacy of irinotecan when given in smaller divided doses compared with large single infusions (9,(35)(36)(37)(38). In addition, this schedule was used in the xenograft studies of this drug combination (21,24) and has been shown to be feasible, safe, and active in the Phase I (10) and II (13) settings.…”
Section: Discussionmentioning
confidence: 99%
“…The formula for Rt is (Vt/Vi) x 100, where Vi is the tumor volume at day 0. Tumor remission is considered when Rt = 50%; Rt = 51-75%: minimum regression; Rt = 76-125%: no variation; Rt > 125%: tumor progression (35,36).…”
Section: Methodsmentioning
confidence: 99%
“…Tumor remission is considered when R t = 50 %; R t = 51-75 %: minimum regression; R t = 76-125 %: no variation; R t [ 125 %: tumor progression [18,19].…”
Section: Tumor Measurements and General Observation Of Micementioning
confidence: 99%